2020
DOI: 10.1101/2020.05.28.20114041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 in environmental samples of quarantined households

Abstract: The role of environmental transmission of SARS-CoV-2 remains unclear. Particularly the close contact of persons living together or cohabitating in domestic quarantine could result in high risk for exposure to the virus within the households. Therefore, the aim of this study was to investigate the whereabouts of the virus and whether useful precautions to prevent the dissemination can be given. 21 households under quarantine conditions were randomly selected for this study. All persons living in each household … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 41 publications
3
63
1
Order By: Relevance
“…New findings from a COVID-19 cohort in Gangelt, Germany, and with cases in Italy provide data on the detection of infectious SARS-CoV-2 on surfaces. Although viral RNA was detected in 3.4% of 119 surface samples in 21 households of confirmed COVID-19-cases and on 7.7% of sampled surfaces around COVID-19-cases in Italy, infectious SARS-CoV-2 was not found in any sample [141,142]. Similar findings were described with SARS-CoV and influenza-virus.…”
Section: Inanimate Surfacessupporting
confidence: 68%
“…New findings from a COVID-19 cohort in Gangelt, Germany, and with cases in Italy provide data on the detection of infectious SARS-CoV-2 on surfaces. Although viral RNA was detected in 3.4% of 119 surface samples in 21 households of confirmed COVID-19-cases and on 7.7% of sampled surfaces around COVID-19-cases in Italy, infectious SARS-CoV-2 was not found in any sample [141,142]. Similar findings were described with SARS-CoV and influenza-virus.…”
Section: Inanimate Surfacessupporting
confidence: 68%
“…23 Neither community study reported positive air samples, although one collected specimens up to 17 days after covid-19 carriers had left the room 25 and the other did not report time of sampling since cleaning or sampling distance from the infected person. 26 These negative studies thus fall substantially short of proving that airborne spread does not occur.…”
Section: Airborne Particle Spread Of Sars-cov-2mentioning
confidence: 99%
“…When using sing a human adenovirus virus (HAdV), Verani et al, 52 found 135 out of 172 surfaces within toilet facilities in a health care setting to be contaminated. Contamination of contact surfaces outside the sanitation setting has been reported in hospitals 55,56,57,58 home settings 59,60,61 and public spaces 60 .…”
Section: Discussionmentioning
confidence: 99%